Subunit composition of α5-containing nicotinic receptors in the rodent habenula - Scholze, Petra (Blackwell Publishing Ltd, 2012)
Gene association studies in humans have linked the α5 subunit gene CHRNA5 to an increased risk for nicotine dependence. In the CNS, nicotinic acetylcholine receptors (nAChRs) that contain the α5 subunit are expressed at relatively high levels in the habenulo-interpeduncular system. Recent experimental evidence furthermore suggests that α5-containing receptors in the habenula play a key role in controlling the intake of nicotine in rodents. We have now analysed the subunit composition of hetero-oligomeric nAChRs in the habenula of postnatal day 18 (P18) C57Bl/6J control mice and of mice with deletions of the α5, the β2, or the β4 subunit genes. Receptors consisting of α3β4* clearly outnumbered α4β2*-containing receptors not only in P18 but also in adult mice. We found low levels of α5-containing receptors in both mice (6%) and rats (2.5% of overall nAChRs). Observations in β2 and β4 null mice indicate that although α5 requires the presence of the β4 subunit for assembling (but not of β2), α5 in wild-type mice assembles into receptors that also contain the subunits α3, β2, and β4.